Perché Carmen non muoia il presente deve cambiare. Spunti di riflessione sul femminicidio - Scarciglia, Miriam (Il sogno della farfalla, 2020)
This article deals with the topic of feminicide. By analysing the historical and cultural roots of gender based violence, the author further investigates the underlying psychopathological dynamics. On the basis of Massimo Fagioli theory, this paper specifically examines the concept of “invisible violence” which remains often unrecognised by those who are subjected to it as it precedes physical aggression for a long time. The main tool to acknowledge this type of violence is sensitivity, experienced in human relationships. This allows to sense movements, gazes, face expressions, tones of voice which are not detected by conscious perception. All these elements, fundamental to deduce the internal reality of the other, can therefore become a real and effective defensive tool.